If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + -2) * 2 = 8 Reorder the terms: (-2 + a) * 2 = 8 Reorder the terms for easier multiplication: 2(-2 + a) = 8 (-2 * 2 + a * 2) = 8 (-4 + 2a) = 8 Solving -4 + 2a = 8 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2a = 8 + 4 Combine like terms: -4 + 4 = 0 0 + 2a = 8 + 4 2a = 8 + 4 Combine like terms: 8 + 4 = 12 2a = 12 Divide each side by '2'. a = 6 Simplifying a = 6
| 8+-19=29 | | x=x-1*(2x-2) | | 30x^2+11-30=0 | | 9x^2=18x^3 | | x=(2x+1-2*1+1)*x-1 | | 7x+40=11x+60 | | 3h+3u=r | | x=(2x+1-(2*1+1))*x-1 | | r=3h+3u | | x^7=128 | | 7-4(2-5y)= | | n^2-25=0 | | (y-2)(y-5)=0 | | (x+2)ln(2)=ln(360) | | 4x+164=12x-12 | | 4x+64=12x-12 | | 114-3x=15x+16 | | 114-3x= | | x=x-2*(2x-4) | | (X-3)(X+6)-10=0 | | 7-7x=159-35x | | X(X-4)-21=0 | | 4y^2-2=12y | | 3(x-3)=3 | | n=4000 | | 7XY^2-5XY(2-Y)=0 | | -9X^2+8X=0 | | 5t+10-6= | | -X^2+11X=0 | | -5X^2-28X+12=0 | | -5X^2-28X=12 | | x^2-x-18=0 |